SET Domain Containing 2 Deficiency in Myelodysplastic Syndrome - Li, Jiaming; Peng, Zhenping; Luo, Fangxiu; Chen, Yu (Frontiers in Genetics, 2020)
Recent studies have shown that myelodysplastic syndrome (MDS) progression to acute myeloid leukemia (AML) is associated with gene mutations. SET domain containing 2 (SETD2) variants were reported as a risk factor of poor prognosis in patients with AML. However, little is known about the potential contribution of SETD2 gene in MDS. In this study, we investigated the roles of SETD2 gene mutations/variants on clinical features and prognosis in patients with MDS. A 43-gene panel was used for next-generation sequencing in 203 patients with primary MDS, and then the effects of SETD2 mutation on Wnt/β-catenin signaling was investigated during the different stages of MDS. At a median follow up of 33 months, 65(32.0%) deaths and 94 (46.3%) leukemic transformations were recorded. The most frequent mutations/variants included TET2, DNMT3A, and ASXL1 mutations/variants. 37 patients had SETD2 gene mutations/variants, and these patients exhibited a significantly increased frequency of TP53 mutations. Multivariate survival analyses indicated that SETD2 mutations/variants were closely associated with overall survival (OS), and they were identified as risk factors for progression-free survival (PFS), especially with low expression of SETD2 gene. Further, we found that SETD2 loss could promote MDS progression via upregulation DVL3 mRNA level in BM cells, and it could also cause genomic instability. Secondary mutations, such as TP53 and FLT3 mutations, were acquired at the time of progression to AML. In conclusion, we showed that SETD2 deficiency was associated with poor outcomes in patients with MDS. Moreover, SETD2 deficiency may upregulate DVL3 expression and modulate genomic stability that caused AML transformation.